3+r=1-r+r

Simple and best practice solution for 3+r=1-r+r equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3+r=1-r+r equation:


Simplifying
3 + r = 1 + -1r + r

Combine like terms: -1r + r = 0
3 + r = 1 + 0
3 + r = 1

Solving
3 + r = 1

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + r = 1 + -3

Combine like terms: 3 + -3 = 0
0 + r = 1 + -3
r = 1 + -3

Combine like terms: 1 + -3 = -2
r = -2

Simplifying
r = -2

See similar equations:

| 2n^9-6n^3+3n^2+6+3n^7+3n^3-6n= | | 121a^2-1=0 | | 4y-7+3y-7= | | 2-33x+2x+9=9 | | y^2+14y+48=0 | | 5x-7y=-16 | | 4x+8+9x-3= | | 2(x^2-5)(x^2+4)=0 | | -5*x+17=-3 | | 27x^4-6x^3+15x^2=0 | | 78-2x=116 | | 4(3p+9)-5=3(12p-5) | | 1+2x=-x-5 | | 3x*9x^2=1 | | 9a^2-49b=0 | | -5*(9-2)+(7*5+7)/6= | | 5+6x=4x+15 | | 3x+(-11y)+(-12x)+7y= | | 18y-21y= | | 6n+7=14 | | x+3x(9)=40 | | 18a=4a-4(a+3) | | 5-7x+6+5x+3x-3=5+2*5 | | 5(3a-1)=-95 | | 2.6x+18=24+22 | | 2.6x+18=24 | | -2m+13=-3 | | 7-9(5x)=20 | | -3(-5k-6)=108 | | 4x*7=49 | | h(t)=1.86t^2+4t-1.86 | | 6+2x=20x |

Equations solver categories